2021
DOI: 10.2166/h2oj.2021.065
|View full text |Cite
|
Sign up to set email alerts
|

Detection and prediction of land use change impact on the streamflow regime in Sahelian river basin, northwestern Nigeria

Abstract: Detecting and predicting the impact of land use/land cover (LULC) changes on streamflow are crucial sources of information for the effective management and protection of land and water resources in Sahelian ecosystems such as the Hadejia river basin. In this study, LULC change detection was performed using ENVI, while the LULC modeling was conducted using the cellular automata (CA)–Markov in the IDRISI environment. However, the streamflow trend and variation were assessed using the Mann–Kendall (MK) trend test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…Also, built-up area increased with 187.84 sq.km, mainly due to the population growth around the basin. This is in line with a similar research carried out by [4], which revealed decrease in grassland and water bodies with an increase in built-up and agricultural land use in northwestern Nigeria basins. There has been an increase in demand for new cultivation land and settlement which in turn resulted in shrinking of other types of land use and land cover of the area.…”
Section: B Discussionsupporting
confidence: 92%
“…Also, built-up area increased with 187.84 sq.km, mainly due to the population growth around the basin. This is in line with a similar research carried out by [4], which revealed decrease in grassland and water bodies with an increase in built-up and agricultural land use in northwestern Nigeria basins. There has been an increase in demand for new cultivation land and settlement which in turn resulted in shrinking of other types of land use and land cover of the area.…”
Section: B Discussionsupporting
confidence: 92%
“…The major causes of transformation is due to conversion of the forest area to newly formed towns and industries in the upper basin. The lacustrine area have augmented from 1.2% to 4% may be due to focused attention of the government for the development of watershed, formation of reservoirs and waterbodies [45].…”
Section: Results Of Land Use Land Cover Classificationmentioning
confidence: 99%
“…This manifests the necessity of future LULC projection for streamflow forecast. It aids in capturing changes in evapotranspiration, land surface features, surface runoff, and land management practices [8,9].…”
Section: Introductionmentioning
confidence: 99%